Increasing Organizational Commitment Through Strengthening Self-Efficacy and Work Involvement - Nancy Yusnita (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2024)
Researches of Organizational Ccommitment had become the popular topic to be one of the main ways to achieve the organizational goal. The objective of this study is to find the strategy to improve.organizational commitment of the employee. This study conducted among employees of Education Office in Bogor, Indonesia. The sample for the study consisted of 107 permanent employees derived randomly from its population. The study mainly utilized quantitative data (from questionnaires). The regression (path analysis) used to find out the relationship among variables. The findings revealed that self-efficacy had a positive and significant effect on organizational commitment. Similarly, job involvement had positive and significant effect on organizational commitment. Research finding also shows that self-efficacy had a positive and significant effect on organizational commitment through job involvement. Based on the research finding, this study proposed some recommendations toward employee at Education Office to strengthen indicators of self-efficacy and job involvement in order to improve employees’organizational commitment.